Congenital adrenal hyperplasia due to 11-beta-hydroxylase deficiency: clinical, biochemical and molecular characteristics and long-term outcomes - Elida Mercado Santis; Ariadna Campos; Paula Fernández; Josep Oriola; Diego Yeste; Víctor Pérez; María Clemente (Anales de Pediatría (English Edition))
Introduction: 11β-hydroxylase (11β-OH) deficiency is the second most frequent cause of classic congenital adrenal hyperplasia (CAH) (5%–8% of cases). Clinically, it is characterized by virilization and arterial hypertension. The objective of this study was to describe the clinical, biochemical and genetic characteristics classic 11β-OH deficiency in patients managed in our hospital and its outcomes. Patients and methods: Retrospective longitudinal, observational and descriptive study. Inclusion criteria: Patients with clinical features of virilization, high levels of 11-deoxycortisol and study of CYP11B1 gene with detection of pathogenic and likely pathogenic variants. Results: We identified 6 patients (1 male, 5 female) from 4 families. In the 4 index cases, the median age at diagnosis was 2.3 years. The 46,XX patients exhibited a variable degree of virilization at diagnosis, with a predominance of Prader stage V, and one case of male sex assignment at birth. All patients had elevated serum concentrations of 17-hydroxyprogesterone and testosterone. Fifty percent of the patients had developed arterial hypertension during the follow-up, with onset at a median age of 9.3 years. Three 46,XX patients reached a median final height of 154 cm. Six different variants of theCYP11B1 gene were identified, 5 of which were novel variants (c.595 G > A, c.710 T > C, c.1156delG, c.395 + 2dupT, c.1159dupA). Conclusions: There is considerable heterogeneity in the clinical presentation of patients with CAH due to 11β-OH deficiency. Early diagnosis and treatment are important to prevent complications and improve long-term outcomes. We report 6 different variants of the CYP11B1 gene, including 5 novel variants. Resumen: Introducción: La deficiencia de 11β-hidroxilasa (11β-OH) es la segunda causa más común de las formas clásicas de hiperplasia suprarrenal congénita (HSC) (5–8% de los casos). Clínicamente se caracteriza por virilización e hipertensión arterial. El objetivo de este estudio es describir las características clínicas, bioquímicas, genéticas y la evolución de los pacientes seguidos en nuestro centro. Pacientes y métodos: Estudio observacional longitudinal, retrospectivo y descriptivo. Criterios de inclusión: clínica de virilización, 11-desoxicortisol elevado en plasma y estudio del gen CYP11B1 con variantes patogénicas y probablemente patogénicas. Resultados: Se identificaron 6 pacientes (1H, 5 M) pertenecientes a 4 familias. La edad media al diagnóstico de los 4 pacientes índice fue de 2.3 años. Las pacientes 46,XX mostraron grados variables de virilización al diagnóstico, predominando el estadio 5 de Prader, con un caso de asignación de género masculino al nacimiento. Todos los pacientes presentaron aumento de las concentraciones séricas de17-hidroxiprogesterona y testosterona. El 50% de los pacientes han desarrollado hipertensión arterial, con una mediana de edad de 9,3 años. Tres pacientes 46,XX han alcanzado talla final con una mediana de 154 cm. Se encontraron 6 variantes diferentes distribuidas a lo largo del gen CYP11B1, 5 de las cuales son variantes no descritas previamente (c.595 G > A, c.710 T > C, c.1156delG, c.395 + 2dupT, c.1159dupA). Conclusiones: Los pacientes con formas clásicas de HSC por déficit de 11β-OH presentan una gran heterogeneidad en la expresión clínica. El diagnóstico y el tratamiento precoces son importantes para prevenir complicaciones y mejorar los resultados a largo plazo.